Hybrid active-passive thermal management system for deep wells: Long-term stability and multi-objective optimization - Zongwei Yao; Haomin Li; Hongxu Xu; Hongfei Yang; Qiushi Bi; Tianshuang Xu (Results in Engineering)
Continuous monitoring of deep Earth parameters is hindered by the thermal instability of electronic devices in high-temperature wells. To address this challenge, this study proposes a hybrid active-passive thermal management system integrating vacuum insulation, phase change materials (PCMs), and an optimized curved flow channel. A multi-objective optimization framework combining Kriging surrogate modeling and NSGA-II algorithm is developed to maximize heat transfer coefficient (h) while minimizing pressure drop (P). Parametric analysis reveals that an 8-channel curved structure with optimized geometry achieves a 20.2% improvement in h and only a 3.4% increase in P, ensuring stable sensor operation below 333 K in 200°C environments for a long time. The proposed system demonstrates superior reliability and compactness, offering a practical solution for long-term deep-well monitoring in geophysical exploration.